The Household Food Security of Internally Displaced Persons (IDPs): An Applied Study on Abushock IDPs Camp, North Darfur State-Sudan (Asian Journal of Social Science Studies, 2016)
This research examined the Household food security of the internally displaced persons in Abou Shock IDPs Camp, North Darfur State – Western Sudan. Data were obtained from both primary and secondary sources. Primary data were obtained from a total 140 of respondents who were selected using multi-stage, stratified sampling technique. Secondary data were obtained from published materials like journals, books and other relevant materials. Data were analyzed using a set of statistical tools such as percentage and frequency tables. Additionally, the Chi-Square technique was used to test whether there is a significant difference or not with respect to be food secured or non-secured and the following socio- demographic and economic variables relating to household head: sex, marital status, family size the educational level, food relief received by household, the number of IDP household members earning money and the number of domestic animals the IDP household owned. The results achieved revealed that %47.8 of the IDP households consumed less than adequate food. Further, the IDPs household food security status in the study area was determined by food relief received by household; the family size; the household ownership of domestic animals, and the number of household members earning money. Accordingly, to increase food consumption at the IDPs households, emphasis must be placed on creating employment opportunities that will increase the number of paid workers among its members, enabling them to possess small domestic animals such as goats, sheep, and poultry either through revolving fund or direct free of charge support.